2017
DOI: 10.1155/2017/1297164
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacological Interventions Targeted at Delirium Risk Factors, Delivered by Trained Volunteers (Medical and Psychology Students), Reduced Need for Antipsychotic Medications and the Length of Hospital Stay in Aged Patients Admitted to an Acute Internal Medicine Ward: Pilot Study

Abstract: Purpose. Effectiveness of nonpharmacological multicomponent prevention delivered by trained volunteers (medical and psychology students), targeted at delirium risk factors in geriatric inpatients, was assessed at an internal medicine ward in Poland. Patients and Methods. Participants were recruited to intervention and control groups at the internal medicine ward (inclusion criteria: age ≥ 75, acute medical condition, basic orientation, and logical contact on admission; exclusion criteria: life expectancy < 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 26 publications
3
33
0
1
Order By: Relevance
“…Donoghue et al () and Giles et al () specified their studies were conducted in aged care wards. There was a variety of participant inclusion criteria across the studies, including participants needing assistance with feeding (Manning et al, ; Roberts et al, ; Robinson et al, ; Walton et al, ), risk of a diagnosis of dementia or delirium (Bateman et al, ; Caplan & Harper, ; Wong et al, ), risk of falls (Donoghue et al, ; Giles et al, ), risk of malnutrition (Huang, Dutkowski, Fuller, & Walton, ), dysphagia (Wright et al, ) and admission for acute conditions (Gorski et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Donoghue et al () and Giles et al () specified their studies were conducted in aged care wards. There was a variety of participant inclusion criteria across the studies, including participants needing assistance with feeding (Manning et al, ; Roberts et al, ; Robinson et al, ; Walton et al, ), risk of a diagnosis of dementia or delirium (Bateman et al, ; Caplan & Harper, ; Wong et al, ), risk of falls (Donoghue et al, ; Giles et al, ), risk of malnutrition (Huang, Dutkowski, Fuller, & Walton, ), dysphagia (Wright et al, ) and admission for acute conditions (Gorski et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The number of volunteers involved in each of the interventions or exposures ranged from 3–128, with three studies providing no information on the number of volunteers (Caplan & Harper, ; Manning et al, ; Wong et al, ). Eight studies provided no information on the type of volunteers used, while the remaining four studies’ volunteers included previous health professionals (Bateman et al, ), student health professionals (Gorski et al, ; Wright et al, ) and college students (Robinson et al, ). The majority of studies reported volunteers were present during weekdays only.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations